2011
DOI: 10.1080/16506073.2011.616531
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Treatment of Depression: A Randomized Controlled Trial Comparing Guided with Unguided Self-Help

Abstract: Internet-delivered self-help for depression with therapist guidance has shown efficacy in several trials. Results from meta-analyses suggest that guidance is important and that self-help programs without support are less effective. However, there are no direct experimental comparisons between guided and unguided internet-based treatments for depression. The present study compared the benefits of a 10-week web-based unguided self-help treatment with the same intervention complemented with weekly therapist suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
316
4
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 361 publications
(361 citation statements)
references
References 42 publications
19
316
4
13
Order By: Relevance
“…30 Our results are also in line with randomised trials done in otherwise healthy patients with depression and without comorbid somatic disorders, which lends support to the usefulness of iCBT in general 31 and speci cally the Deprexis programme in patients with major depressive disorder. 18,32,33 Few randomised trials have assessed the e ects of pharmacological or behavioural interventions to treat depression in patients with multiple sclerosis. Findings from studies using antidepressant pharmacotherapy in this population have suggested some e cacy but also indicatedfrequentside-e ects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Our results are also in line with randomised trials done in otherwise healthy patients with depression and without comorbid somatic disorders, which lends support to the usefulness of iCBT in general 31 and speci cally the Deprexis programme in patients with major depressive disorder. 18,32,33 Few randomised trials have assessed the e ects of pharmacological or behavioural interventions to treat depression in patients with multiple sclerosis. Findings from studies using antidepressant pharmacotherapy in this population have suggested some e cacy but also indicatedfrequentside-e ects.…”
Section: Discussionmentioning
confidence: 99%
“…19 Email support might also be useful. 33 Therefore, the e cacy of interventions such as Deprexis in multiple sclerosis might be further enhanced by adding therapist support in one form or another. Whether or not this is indeed bene cial remains to be tested in future studies and is an active area of investigation in our research.…”
Section: Discussionmentioning
confidence: 99%
“…Synchronous communication can be used in adherence management after the non-response to asynchronous strategies or for urgent cases like deterioration. However, more research is needed to determine how the content, length, and frequency of therapists' messages can affect outcome in guided self-help treatments [75]. On the other hand, because of the oscillating course of depression, it is suggested to monitor depression symptoms and to add a crisis link in the web-site.…”
Section: Discussion Principal Results and Comparison With Previous Workmentioning
confidence: 99%
“…Nonetheless, a study that compared this treatments within the same trial, comparing the benefits of a 10-week web-based unguided self-help treatment for depression (n=25) with the same intervention complemented with weekly therapist support via e-mail, found no significant differences in participant's intervention completion (or symptom reduction) [75]. Authors discuss that the lack of significant differences in relation of the stringent inclusion criteria (Beck Depression Inventory-II > 13), the telephone structured diagnostic interview made at selection and the content of the feedback provided by therapists which was mainly generic and brief.…”
Section: Adherence Managementmentioning
confidence: 99%
See 1 more Smart Citation